2017
DOI: 10.1002/bkcs.11129
|View full text |Cite
|
Sign up to set email alerts
|

3‐Amino‐1H‐pyrazolopyridine Derivatives as a Maternal Embryonic Leucine Zipper Kinase Inhibitor

Abstract: Maternal embryonic leucine zipper kinase (MELK) has been implicated in various cellular processes and is highly upregulated in diverse cancers, then it is thought to be a promising anticancer target. 3‐Anilino‐1H‐pyrazolo[3,4‐b]pyridine scaffold was identified as a novel scaffold for MELK kinase inhibitors in high throughput screening (HTS). From exploration for structure–activity relationship (SAR) studies mainly by the modification of the 3 (C3), and 5‐positions (C5), 4‐(4‐methylpiperazin‐1‐yl)‐N‐{5‐[1‐(pipe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Thus, MELK can be considered as a crucial target for cancer treatment. In view of this, Park et al designed and synthesized piperidine-bearing pyrazolopyridine scaffolds as potent MELK inhibitors (Park et al, 2017). An excellent anti-MELK profile has been noticed for evaluated molecules.…”
Section: Pyridine/piperidine Derivativesmentioning
confidence: 99%
“…Thus, MELK can be considered as a crucial target for cancer treatment. In view of this, Park et al designed and synthesized piperidine-bearing pyrazolopyridine scaffolds as potent MELK inhibitors (Park et al, 2017). An excellent anti-MELK profile has been noticed for evaluated molecules.…”
Section: Pyridine/piperidine Derivativesmentioning
confidence: 99%
“…Moreover, pyrazolopyridine-derived drug molecules exhibit anti-cancer properties (Huang et al, 2007;Ye et al, 2009). They are inhibitors of several important proteins, namely cyclinedependent kinase1, HIV reverse transcriptase, leucine zipper kinase, protein kinase, xanthine oxidase, interleukin-6 (IL-6), tumor necrosis factor alpha (TNF-), phosphodiesterase-4, NAD(P)H oxidases (Kumar et al, 2019;Gö khan-Kelekçi et al, 2007;Fathy et al, 2015;Park et al, 2017). A recent study reported that they could be promising inhibitors against the enzyme pantothenate synthetase from Mycobacterium tuberculosis (Amaroju et al, 2017).…”
Section: Chemical Contextmentioning
confidence: 99%
“…For instance, 6-(3,5-dimethoxyphenyl)-3-(4-fluorophenyl)-1H-pyrazolo [3,4-b]pyridine (APcK110) is an extensively researched Kit kinase inhibitor [32][33][34]. More recently, various 1H-pyrazolo [3,4b]pyridine derivatives were reported as potent ALK-L1196M [35] and CDK8 inhibitors [36], PPARα agonists [37], and antimicrobial, anti-quorum-sensing, and anticancer agents [38], while 3-amino-1H-pyrazolo [3,4-b]pyridine core was identified as a novel scaffold for MELK kinase inhibitors [39]. 2-{[2-(1H-Pyrazolo [3,4-c]pyridin-3-yl)-6-(trifluoromethyl)pyrimidin-4-yl]amino}ethanol is a bacterial DNA ligase inhibitor [40], several compounds bearing 1H-pyrazolo [4,3-b]pyridin-3-amine scaffold act as positive allosteric modulators of the metabotropic glutamate receptor 4 (mGlu 4 ) [41,42], 3-phenylpyrazolo [3,4-c]pyridines were reported to possess antiproliferative activity [43], and 1-(4-methoxybenzyl)-7-(4methylpiperazin-1-yl)-N-[4-(4-methylpiperazin-1-yl)phenyl]-3-phenyl-1H-pyrazolo [3,4c]pyridin-5-amine was suggested as potential angiogenesis inhibitor [44].…”
Section: Introductionmentioning
confidence: 99%